Characterization and identification of rhizobacteria associated with Liberica and Robusta coffee rhizosphere - Glenn Vince D. Navarro; Daisyree D. Quirong; Garrison A. Maghanoy; Angelbert D. Cortes (Technology in Horticulture)
Coffee is a viable agricultural commodity that makes a positive impact to the Philippine economy. However, with an increasing trend in domestic consumption, the local coffee production has declined. Chemical fertilization has been considered by many farmers to improve coffee production and yield but it causes a serious threat to public health and the environment. Biofertilizer using rhizobacteria has beneficial effects to improve the growth and yield of many crops, which is cost effective and safer than synthetic fertilizers. This study characterized the indigenous and beneficial rhizobacteria obtained from the Liberica and Robusta coffee rhizosphere, in terms of phosphate solubilization, biocontrol activities, and tolerance to abiotic stresses. Six rhizobacterial isolates were molecularly identified and belonged to genera Bacillus, Burkholderia, and Pantoea. These rhizobacteria solubilized inorganic phosphate with solubilization index ranging from 2.5 to 3.5 mm. For biocontrol activities, Bacillus sanguinis showed activity in terms of HCN and multiple hydrolytic enzymes production. Also, Burkholderia sp. demonstrated amylase, protease, and pectinase activities. Moreover, all isolates were found to be relatively tolerant to a wide range of pH and concentrations of salt and heavy metals. The performance of these rhizobacterial isolates in terms of phosphate solubilization, biocontrol activities, and tolerance to stresses is promising and shown to have potential in coffee cultivation in the Philippines.